Make in India: Promoting Manufacturing and Investments in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Make in India is an initiative launched by the Government of India to encourage multi-national, as well as national companies to manufacture their products in India. It was launched by Prime Minister of India on 25 September 2014. This is an international marketing strategy conceptualized by the PM of India to attract investments from Businesses all over the world and transforming India into a global manufacturing Hub. For promoting this campaign the web portal, logo and brochures are used for detailing 25 priority sectors of the economy. The major objective behind the initiative is to focus on job creation and skill enhancement in 25 sectors of the economy. The initiative also aims at high quality standards and minimising the impact on the environment. The initiative hopes to attract capital and technological investment in India. Through Make in India initiative, government will focus on building physical infrastructure as well as creating a digital network to make India a global hub for manufacturing of goods ranging from cars to soft wares, satellites to submarines, pharmaceuticals to ports and paper to power.